Durio Zibethinus Murr. Peel and Zeolite In Reducing the Hardness of Water - Sri Poerwati; Siti Nabila Namiroh; Mujiyono Mujiyono (Jurnal Teknokes, 2022)
Hardness is water that contains metals or cations with two valences, especially calcium (Ca) and magnesium (Mg). Excessive hard water can cause detergents to not easily foam, be corrosive to household furniture and interfere with health such as kidney stone disease. This study aimed to test the filtration ability of a combination of Durio zibethinus Murr. peel activated charcoal with zeolite to reduce hardness in water. This study was a true experimental study with a pretest-posttest control group design using three variations of Durio zibethinus Murr. peel thickness 7 cm, 9 cm, 11 cm and zeolite 70 cm. The sampling method used was grappample with 9 replications and analyzed using the Anova statistical test. The results of the filtration hardness of the combination of Durio zibethinus Murr. peel activated charcoal) and zeolite 70 cm thickness with a thickness of 7 cm activated charcoal obtained an average of 107.18 mg/l. The thickness of activated charcoal 9 cm on average was 88.74 mg/l. The thickness of activated charcoal 11 cm on average was 71.40 mg/l. The result of One Way Anova statistical test (0.000) is smaller than (0.05), so the hypothesis is accepted. So there is a difference in the decrease in water hardness in variations in the thickness of the media for Durio zibethinus Murr. peel activated charcoal and zeolite. In future research, the thickness of Durio zibethinus Murr. peel activated charcoal (Durio zibethinus Murr.) and the thickness of zeolite which is more effective in reducing hardness can be determined, using Durio zibethinus Murr. peel activated charcoal and zeolite filtration by flowing water into the pipe for 5 minutes and performing further treatment of water to make it clear.